Earnings losses and labor mobility over the lifecycle - Philip Jung; Nikolas Moritz Kuhn (Institute for the Study of Labor (IZA), 2012)
Extensive literature demonstrates that workers with high tenure suffer large and persistent earnings losses when they are displaced. We study the reasons behind these losses in a tractable search model that includes a lifecycle dimension, endogenous job mobility, and worker- and match-heterogeneity. The model jointly explains key characteristics of the U.S. labor market such as large average transition rates, a large share of stable jobs, and earnings losses after displacement. We decompose earnings losses and find that only 50% result from wage loss, and endogenous reactions and selection account for the remainder. These findings have important implications for welfare costs of displacement and labor market policies.
Keywords: E24; J63; J64; 330; earnings losses; lifecycle; labor-market transitions; turbulence; Verdienstausfall; Arbeitsmobilität; Lebensverlauf; Arbeitsuche; USA